A facile and fast approach to mechanically stable and rapid self-healing waterproof fabrics. (23rd March 2016) - Li, Yong; Ge, Bo; Men, Xuehu; Zhang, Zhaozhu; Xue, Qunji
Abstract: The design of multifunctional materials with durability under extreme conditions has raised considerable interest for their highly practical potential. Thus, we developed an efficient and technically simple method to prepare easily repairable and rapid self-healing superhydrophobic fabrics, which only involves one-step coating of polyfluorowax (PFW)/graphite fluoride (GF) complexes. The resulting waterproof fabrics can be easily repaired without any complicated and expensive fabrication procedures. Importantly, the fabrics with a self-healing function can rapidly and repetitively restore the superhydrophobicity when the hydrophobicity is damaged owing to the regenerated fresh surface on the fibers induced by heating. Furthermore, the fabrics can maintain their water repellency even was seriously damaged during the abrasion and mechanical stretch tests. In addition, the self-healing fabric can be further dyed and still exhibits satisfactory durability against strong acidic or alkaline, high temperature and humidity, freezing environment and long-term UV exposure. Graphical abstract: